Spectrum slicing of a broadband light source - Mohamed Shabeer, Mohamed Shabeer (2006)
Since the inception of optical fiber communication in 1974, their transmission capacity has experienced a tremendous increase in the years after. Several technology advances spurred its growth. But its use was kept to long haul applications like intercity links and international links, because of its initial capital cost. The use of Wavelength Division Multiplexing offered a further boost in fiber transmission capacity. The basis of WDM was to use multiple sources operating at slightly different wavelengths to transmit several independent information streams over the fiber. Laser diodes were the traditionally used sources because of its narrow spectral width which in turn reduces the losses and gives out light with more power which is used to carry data over a long range. But, in today’s era where data rate is of more importance, immaterial of whether it is long or short haul, a technology was required which will make the short haul communication using optics, cheaper and affordable. Thus Light Emitting Diode was forced to play the role of light source instead of the laser. But since LED is having a very broad spectrum, most of its power would be wasted. So a technique called Spectral Slicing was brought up to nullify this aspect of LED so as to be useful in WDM systems. By using LED the cost of the system will also be kept low. This work here, demonstrates the spectral slicing technique which can be used in WDM systems. The slicing component used here is a Tunable Band-pass Filter. The output power received using this method was compared with another method which was done using Arrayed Waveguide Grating (AWG) and also with a mathematical model. Power budget analysis is done where by, the probable link distance that a system using spectral slicing technique by tunable band-pass filters, can cover is found to be about 15-30 km. Also, a cost based analysis is done, using the common market prices of the major components, to prove that this technique reduces the cost to an extend that the need for lasers is never inevitable in the case of short haul communications